A photovoltaic–hydrovoltaic-coupled carbon-based, all-inorganic CsPbBr3 perovskite solar cell. Issue 31 (28th March 2023) - Tan, Jin; Dou, Jie; Tang, Qunwei
Abstract : A physical proof-of-concept carbon-based, all-inorganic Cs0.91 Rb0.09 PbBr3 PSC is made by coupling photovoltaic and hydrovoltaic effects to harvest solar energy and steam energy. Abstract : A photovoltaic–hydrovoltaic-coupled carbon-based, all-inorganic Cs0.91 Rb0.09 PbBr3 perovskite solar cell achieved a peak power conversion efficiency of 9.40% under one sun illumination and a maximum voltage of 0.39 V and current of 1.40 μA in a flowing vapor atmosphere.